Effect of the Pitot Tube on Measurements in Supersonic Axisymmetric Underexpanded Microjets - Sergey G. Mironov; Vladimir M. Aniskin; Tatiana A. Korotaeva; Ivan S. Tsyryulnikov (Micromachines, 2019)
This paper describes the results of methodical investigations of the effect of the Pitot tube on measurements of gas-dynamic parameters of supersonic axisymmetric underexpanded real and model microjets. Particular attention is paid to distortions of Pitot pressure variations on the jet axis associated with the wave structure of the jet and to distortions of the supersonic core length. In experiments with model jets escaping from nozzles with diameters ranging from 0.52 to 1.06 mm into the low-pressure chamber, the measurements are performed by the Pitot tubes 0.05 to 2 mm in diameter. The results are analyzed together with the earlier obtained data for real microjets escaping from nozzles with diameters ranging from 10 to 340 µm where the parameters of real microjets were determined by the Pitot microtube 12 µm in diameter. Interaction of the Pitot tube with an unsteady jet in the laminar-turbulent transition region is investigated; the influence of this interaction on Pitot pressure measurements is determined, and a physical interpretation of this phenomenon is provided.